CD4 cell count response to first-line combination ART in HIV-2+ patients compared with HIV-1+ patients: a multinational, multicohort European study. (17th July 2017) - Wittkop, Linda; Arsandaux, Julie; Trevino, Ana; Schim van der Loeff, Maarten; Anderson, Jane; van Sighem, Ard; Böni, Jürg; Brun-Vezinet, Françoise; Soriano, Vicente; Boufassa, Faroudy; Brockmeyer, Norbert; Calmy, Alexandra; et al.
Abstract: Background: CD4 cell recovery following first-line combination ART (cART) is poorer in HIV-2+ than in HIV-1+ patients. Only large comparisons may allow adjustments for demographic and pretreatment plasma viral load (pVL). Methods: ART-naive HIV+ adults from two European multicohort collaborations, COHERE (HIV-1 alone) and ACHIeV2e (HIV-2 alone), were included, if they started first-line cART (without NNRTIs or fusion inhibitors) between 1997 and 2011. Patients without at least one CD4 cell count before start of cART, without a pretreatment pVL and with missing a priori -defined covariables were excluded. Evolution of CD4 cell count was studied using adjusted linear mixed models. Results: We included 185 HIV-2+ and 30321 HIV-1+ patients with median age of 46 years (IQR 36–52) and 37 years (IQR 31–44), respectively. Median observed pretreatment CD4 cell counts/mm 3 were 203 (95% CI 100–290) in HIV-2+ patients and 223 (95% CI 100–353) in HIV-1+ patients. Mean observed CD4 cell count changes from start of cART to 12 months were +105 (95% CI 77–134) in HIV-2+ patients and +202 (95% CI 199–205) in HIV-1+ patients, an observed difference of 97 cells/mm 3 in 1 year. In adjusted analysis, the mean CD4 cell increase was overall 25 CD4 cells/mm 3 /year lower (95% CI 5–44; P  =   0.0127) in HIV-2+ patients compared with HIV-1+ patients. Conclusions: A poorer CD4 cell increase during first-line cART was observed in HIV-2+ patients, even after adjusting for pretreatment pVL and other potential confounders. Our results underline the need to identify more potent therapeutic regimens or strategies against HIV-2.